2014
DOI: 10.1007/s00415-014-7583-5
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery stenosis in the Basilar Artery International Cooperation Study (BASICS): prevalence and outcome

Abstract: We assessed the prevalence of vertebral artery (VA) stenosis or occlusion and its influence on outcome in patients with acute basilar artery occlusion (BAO). We studied 141 patients with acute BAO enrolled in the Basilar Artery International Cooperation Study (BASICS) registry of whom baseline CT angiography (CTA) of the intracranial VAs was available. In 72 patients an additional CTA of the extracranial VAs was available. Adjusted risk ratios (aRRs) for death and poor outcome, defined as a modified Rankin Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
1
10
0
3
Order By: Relevance
“…In comparison, the long-term stroke recurrence after carotid stenting is around 7% 13. Overall treatment numbers for intracranial posterior circulation stenosis were low in all trials: VAST 9 (of 57) patients,9 VIST 13 (of 61) patients10 and SAMMPRIS 36 patients 6…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In comparison, the long-term stroke recurrence after carotid stenting is around 7% 13. Overall treatment numbers for intracranial posterior circulation stenosis were low in all trials: VAST 9 (of 57) patients,9 VIST 13 (of 61) patients10 and SAMMPRIS 36 patients 6…”
Section: Discussionmentioning
confidence: 95%
“…One patient died of stroke in another territory and five patients succumbed to other causes. In comparison, the VAST and VIST trials reported stroke recurrence rates of 12% and 8.2% during follow-up of 3 and 3.5 years, respectively 9 10. However, in both trials intracranial and extracranial vertebrobasilar stenoses were pooled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11] Most are descriptions of symptomatic stenosis with vertebro-basilar posterior cranial fossa manifestations. [5][6][7] 20% of strokes are caused by vertebral artery stenosis. 8 The prevalence of vertebral artery stenosis without vertebro-basilar symptoms, as in this case, is poorly quantified, though studies put it at approximately 8%.…”
Section: Vertebral Artery Abnormalitiesmentioning
confidence: 99%